Athlete mental health and mental illness in the era of COVID-19: shifting focus with a new reality - Edwards, C.; Thornton, J. (British Journal of Sports Medicine, 2020)
Few events in history have altered the staging of the Olympic Games. Thus far only the World Wars have kept our athletes away from the grand stage, and several politically based boycotts prevented some nations from participating in other Olympic Games. In fact, few events have altered day-to-day function across the globe as has COVID-19. In what seems like an instant we have gone from training and congregating wherever and whenever we want- to travel restrictions, closed borders, closed training centers, and millions of people living in self-isolation.